Coronary Artery Disease and the Profile of Cardiovascular Risk Factors in South South Nigeria: A Clinical and Autopsy Study - Okon Ekwere Essien; Joseph Andy; Victor Ansa; Akaninyene Asuquo Otu; Alphonsus Udoh (Cardiology Research and Practice)
Introduction. Death from coronary artery disease (CAD) has been until recently considered rare in Nigeria. We present a report of a study of CAD with its predisposing cardiovascular (CVD) risk factors in South South Nigeria. Methods. We examined the autopsy reports of 747 coroner cases and 41 consecutive clinically diagnosed cases of ischemic heart disease seen in South South Nigeria. Results. CAD was diagnosed in 13 (1.6%) of 747 autopsies. They were predominantly males, urban residents, and of high social class with combination of CVD risk factors of hypertension, alcohol use, diabetes mellitus, cigarette smoking, poor physical activities, and obesity. The mean serum cholesterol of the clinical subjects was 4.7±1.57 mmol/L and 5.07±1.94 mmol/L for angina and myocardial infarction, respectively, which was higher than the mean total cholesterol for locality of 3.1 mmol/L. Conclusion. CAD and its risk factors are contributing to mortality and morbidity in South South Nigeria. These risk factors include hypertension, alcohol use, diabetes mellitus, cigarette smoking, poor physical activity, and obesity. Nigerians in this locality with CAD have raised serum lipids.